2013
DOI: 10.1177/1534765612441978
|View full text |Cite
|
Sign up to set email alerts
|

Predeployment mental health and trauma exposure of expatriate humanitarian aid workers: Risk and resilience factors.

Abstract: Expatriate aid workers (n = 214) representing 19 nongovernmental organizations (NGOs) completed a predeployment survey, including measures of mental health (depression, anxiety, and posttraumatic stress disorder [PTSD]); risk factors (childhood trauma, family risk, and adult trauma exposure); and resilience factors (coping, social support, and healthy lifestyle) to assess their baseline mental health during preparation for deployment. Multiple regression analysis indicated that childhood trauma/family risk was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 25 publications
1
62
1
1
Order By: Relevance
“…The small number of trauma responses in the present study is not an indication of the low impact of trauma. Aid workers experience an elevated risk of trauma (Stoddard et al 2009) which can have enduring impacts long after other stressors have receded (Eriksson et al 2012). However, the results of the present study suggest that other stressors are more common and are likely to be detrimental to aid worker wellbeing.…”
Section: Discussioncontrasting
confidence: 47%
“…The small number of trauma responses in the present study is not an indication of the low impact of trauma. Aid workers experience an elevated risk of trauma (Stoddard et al 2009) which can have enduring impacts long after other stressors have receded (Eriksson et al 2012). However, the results of the present study suggest that other stressors are more common and are likely to be detrimental to aid worker wellbeing.…”
Section: Discussioncontrasting
confidence: 47%
“…That is, before entering the field, the trainee group displayed attributes, behaviours and perceptions that have previously been shown to mediate mental health sequelae among HA worker populations, notably anxiety, burnout and PTSD Brooks et al 2015;Comoretto et al 2015;Eriksson et al 2012). This study found that the four factors, motivation and achievement, evolving ideas of HA, social support, and help-seeking attitudes and behaviours, represent potential mediating factors among these trainees.…”
Section: Discussionmentioning
confidence: 97%
“…Social support represents an important protective factor against adverse mental health effects for the general population, as it appears to provide an effective buffer against stressful experiences Brooks et al 2015;Cardozo et al 2012;Eriksson et al 2012;Musa and Hamid 2008). Social support is defined as emotional and instrumental social interactions that provide an individual with actual assistance or a belief that such assistance is available (Thoits 2011;Hobfoll 1988).…”
Section: Social Support and Help-seekingmentioning
confidence: 99%
“…Valuable work previously highlighted stresses experienced by expatriate (international) workers employed by nongovernmental organizations (NGOs) to deliver humanitarian aid or facilitate development projects (Ehrenreich and Elliott 2004;Eriksson et al 2013). Others have isolated experiences of in-country (national) field workers challenged with balancing donor and organizational demands with localized conditions and power structures (Suparamaniam and Dekker 2003;Lopes Cardozo et al 2005;Shah et al 2007;Musa and Hamid 2008).…”
Section: Introductionmentioning
confidence: 99%